2020
DOI: 10.1017/can.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

Skepticism Motivated: On the Skeptical Import of Motivated Reasoning

Abstract: Empirical work on motivated reasoning suggests that our judgments are influenced to a surprising extent by our wants, desires, and preferences (Kahan 2016; Lord, Ross, and Lepper 1979; Molden and Higgins 2012; Taber and Lodge 2006). How should we evaluate the epistemic status of beliefs formed through motivated reasoning? For example, are such beliefs epistemically justified? Are they candidates for knowledge? In liberal democracies, these questions are increasingly controversial as well as politically timely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…(Richard Buckminster Fuller) 1 Many studies have shown that people frequently engage in politically motivated cognition: we often tend to conform our assessments and beliefs about information to our political goals and political identity rather than to accuracy (Kunda 1990;Taber and Lodge 2006;Nisbet et al 2015;Kahan 2016). Politically motivated cognition, which is taken to be less than fully epistemically rational because it involves a diminished sensitivity to facts (Huemer 2016;Ringel et al 2019), has recently become a hot topic in philosophy (Gerken 2019;Peters 2019;Talisse 2019;Carter and McKenna 2020). The present paper offers a social epistemological investigation of a specific type of politically motivated cognition.…”
Section: Introductionmentioning
confidence: 94%
“…(Richard Buckminster Fuller) 1 Many studies have shown that people frequently engage in politically motivated cognition: we often tend to conform our assessments and beliefs about information to our political goals and political identity rather than to accuracy (Kunda 1990;Taber and Lodge 2006;Nisbet et al 2015;Kahan 2016). Politically motivated cognition, which is taken to be less than fully epistemically rational because it involves a diminished sensitivity to facts (Huemer 2016;Ringel et al 2019), has recently become a hot topic in philosophy (Gerken 2019;Peters 2019;Talisse 2019;Carter and McKenna 2020). The present paper offers a social epistemological investigation of a specific type of politically motivated cognition.…”
Section: Introductionmentioning
confidence: 94%
“…14 What is the epistemic status of a person's belief that is not the result of motivated reasoning but that the person does not have strong reason to think is not the result of motivated reasoning? (Carter & McKenna, 2020). Is motivated reasoning something that one who aspires for epistemic excellence should try to preempt?…”
Section: What Is the Epistemic Significance Of Motivated Reasoning?mentioning
confidence: 99%
“…If I come to believe that human cognition in general is much more impacted by motivated reasoning than I had realized, would it be irresponsible not to reduce the confidence of my beliefs in general, or of particular domains of belief, such as political beliefs? 14 What is the epistemic status of a person's belief that is not the result of motivated reasoning but that the person does not have strong reason to think is not the result of motivated reasoning? (Carter & McKenna, 2020). Is motivated reasoning something that one who aspires for epistemic excellence should try to preempt?…”
Section: Implications For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“… See also Carter and McKenna (2020) for a discussion of politically motivated reasoning. Although they sketch the possible skeptical implications of such reasoning, they refrain from evaluating the plausibility of such implications. …”
mentioning
confidence: 99%